Addition of Camellia sinensis extract to water to disinfect respiratory viruses accumulated over different surfaces. (22nd June 2022) - Abd-ElShafy, Dina Nadeem; Nadeem, Rola; Bahgat, Mahmoud Mohamed
Abstract: New precautions have become part of our daily life since COVID-19 pandemic such as wearing masks, maintaining distance and disinfecting products bought from markets before using them which is exhausting. We aimed to test the inhibitory effect of Camellia sinensis (black tea) water extracts on respiratory viruses and the inhibition of viruses accumulated over different surface types after being soaked in water supplemented with the extracts. Two water extraction methods (extract A: maceration at 80 °C for 30 min and extract B: boiling for 40 min) were applied; extracts were analyzed by high-performance liquid chromatography to detect polyphenolic compounds. Results showed that 200 μg/ml of extract A and 50 μg/ml of extract B in water caused 100% inhibition of influenza A (enveloped virus) virus after 1.5 h and similar results were obtained for adenovirus (non-enveloped virus) but at the same concentration of extract A and at 100 μg/ml of extract B. Different surfaces (aluminum, glass, plastic or carton, vegetables of smooth (tomato) or rough (lemon) surfaces and green leaves) were inoculated with both viruses for 20 min and then soaked in the water supplemented with 200 μg/ml of extract A or 100 μg/ml of extract B for 1.5 h, and this resulted in complete inhibition of both viruses. HIGHLIGHTS: Extracts of natural product represent a treasure of compounds that can work synergistically together better and cheaper than being isolated. Water extracts of Camellia sinenses plant have a lot of polyphenolic compounds beside tannins that have direct inhibitory effect on tested viral particles. Soaking substances of different surface natures in water containing that extract cause inhibition to accumulated viral particles on those surfaces within 1.5 hours. This can be of great benefit during COVID-19 pandemic where accumulated viruses on surfaces bought from markets represent source of infection. Graphical Abstract